A Land-use Approach for Capturing Future Trip Generating Poles - Stamos, Iraklis; Georgia, Aifadopoulou; Mitsakis, Evangelos; Morfoulaki, Maria; Tamiakis, Iasonas (TeMA - Journal of Land Use, Mobility and Environment, 2015)
Changes in the usage of a particular urban or regional area have immediate effects on transportation, such as the development of a new multimodal terminal within a city, or the creation of a business park in its outskirts. Thus far, this correlation has been under-researched at a national level in Greece. As a result, its effects on trip generation and passenger flows has been underestimated at the planning level, leading to the implementation of projects that are neither viable nor sustainable. This paper proposes that land use changes ought to be considered in tandem with transport-related changes at the planning stage. To this effect, we present a three-step methodology for an integrated approach to capturing future trip generation: the identification of future trip-generating poles within the study area; the development of scenarios related to the probability of these changes occurring and their potential magnitude; an estimation of future trends in passenger flows. The methodology is applied to the Metropolitan area of Thessaloniki, Greece. Using data obtained from development plans, national statistical services and research projects’ and studies’ findings, we estimate future trip-generation subsequent to land use change. Data is processed and evaluated by a local experts’ group, representing various key-disciplines of the area’s planning stakeholders.